Targeting as an enabling factor in NATO military operations (Journal of the Spanish Institute for Strategic Studies, 2021)
The conflicts of this new century are influenced by the complexity of the global socio-political scenario, rapid technological and doctrinal development or necessary compliance with international law. This changing scenario, among many other factors, greatly influences the planning of a military operation. Understanding the course of the last century’s history provides a historical context that explains the reason –and the need– for NATO’s 2010 organisational model; as well as the creation of the concept of targeting and its subsequent integration into the Alliance’s organisational structure. This paper reviews targeting from a holistic perspective –doctrinal, legal and military innovation– in order to determine whether this concept fulfils anenabling role within NATO’s military operation planning process.
Keywords: Targeting; military operation; capability; innovation; JFAC; NATO